2017
DOI: 10.1016/j.amjmed.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Headache and Long-Term Cardiovascular Outcomes: An Extended Follow-Up of the Women's Ischemia Syndrome Evaluation

Abstract: Among women being evaluated for ischemic heart disease, those reporting a history of migraine headache had increased risk of future cardiovascular events on long-term follow-up. This risk was primarily driven by a more-than twofold increase in the risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…No overall association was found in a 2011 meta-analysis of five pooled studies [10]. More recently, no association with all-cause mortality was observed in two large cohort studies [11,12]. A recent Taiwanese study found that people with migraine had lower all-cause mortality than individuals without migraine, though this study did only captured in-hospital mortality and many important sources of confounding may have been omitted by the variable selection process [13].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…No overall association was found in a 2011 meta-analysis of five pooled studies [10]. More recently, no association with all-cause mortality was observed in two large cohort studies [11,12]. A recent Taiwanese study found that people with migraine had lower all-cause mortality than individuals without migraine, though this study did only captured in-hospital mortality and many important sources of confounding may have been omitted by the variable selection process [13].…”
Section: Introductionmentioning
confidence: 87%
“…Migraine and non-migraine headache have not been consistently linked with an increased risk of all-cause mortality [10][11][12]. Some studies even suggested a decreased risk [20].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Globally, migraines are approximately twice as prevalent in females as in males, particularly affecting young and middle-aged females with menstrual cycles [ 3 , 4 , 5 ]. Migraines affect the central nervous system and impair daily life for those affected, cause comorbid psychological conditions, and increase the risk of cardiovascular diseases for patients [ 6 , 7 ]. Investigations continue regarding the detailed mechanism and risk factors for migraines.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the diagnosis of migraine have a 1.5 times greater risk of developing acute myocardial infarction, angina, and stroke,22 which increases mortality by cardiovascular diseases by 1.37 times 23. The main risk is related to cerebral ischemia 24 , 25…”
Section: Discussionmentioning
confidence: 99%